Pengaruh Pengalaman Investasi, Risk Tolerance, dan Influencer Sosial Media terhadap Keputusan Investasi dengan Literasi Keuangan sebagai Variabel Moderasi - Jumiyani Jumiyani; Edi Wibowo; Ririn Indriastuti (Universitas 45 Surabaya, 2024)
The aim of this research is to analyze the effect of investment experience, risk tolerance, and social media influencers on investment decisions with financial literacy as a moderating variable. The population in this study were capital market investors in Surakarta City but the exact number of investors was unknown The sampling technique used was purposive sampling. The results of the analysis state that investment experience has a positive and insignificant effect on generation Z investment decisions in Surakarta City because it has an original sample coefficient value of 0.094 (positive), t-statistic value 1.314 < 1.96 and P-value 0.189 ≥ 0.05, risk tolerance has a positive and insignificant effect on generation Z investment decisions in Surakarta City because it has an original sample coefficient value of 0.014 (positive), t-statistic 0.162 < 1.96 and P-value 0.871 ≥ 0.05, social media influencers have a positive and significant effect on generation Z investment decisions in Surakarta City because they have an original sample coefficient value of 0, 282 (positive), t-statistic 2.468 > 1.96 and P-value 0.014 < 0.05, financial literacy does not moderate the effect of investment experience on investment decisions because it has an original sample coefficient value of -0.071 (negative), t-statistic 1.320 < 1.96 and P-value 0.187 ≥ 0.05, financial literacy moderates the effect of risk tolerance on investment decisions because it has an original sample coefficient value of 0.247 (positive), t-statistic 3.130> 1.96 and P-value 0.002 < 0.05, financial literacy moderates the influence of social media influencers on investment decisions because it has a coefficient value of -0.173 (negative), t-statistic 2.237> 1.96 and P-value 0.026 < 0.05.